Design, synthesis, and evaluation of bioactive molecules; Quantification of tricyclic pyrones from pharmacokinetic studies; Nanodelivery of siRNA; and Synthesis of viral protease inhibitors - Weerasekara, Sahani Manjitha (Kansas State University, 2016)
Four research projects were carried out and they are described in this dissertation. Glycogen synthase kinase-3 beta (GSK3β) plays a pivotal and central role in the pathogenesis of Alzheimer's disease (AD) and protein kinase C (PKC) controls the function of other proteins via phosphorylation and involves in tumor promotion. In pursuit of identifying novel GSK3β and/or PKC inhibitors, substituted quinoline molecules were designed and synthesized based on the structure-activity-relationship studies. Synthesized molecules were evaluated for their neural protective activities and selected molecules were further tested for inhibitory activities on GSK3β and PKC enzymes. Among these compounds, compound 2 was found to have better GSK3β enzyme inhibitory and MC65 cell protection activities at low nanomolar concentrations and poor PKC inhibitory activity whereas compound 3 shows better PKC inhibitory activity. This demonstrates the potential for uses of quinoline scaffold in designing novel compounds for AD and cancer. Pharmacokinetics and distribution profiles of two anti-Alzheimer molecules, CP2 and TP70, discovered in our laboratory were assessed using HPLC/MS. Plasma samples of mice and rats fed with TP70 via different routes over various times were analyzed to quantify the amounts of TP70 in plasma of both species. Distribution profiles of TP70 in various tissues of mice were studied and results show that TP70 penetrated the blood brain barrier and accumulated in the brain tissue in significant amounts. Similarly, the amount of CP2 in plasma of mice was analyzed. The HPLC analysis revealed that both compounds have good PK profiles and bioavailability, which would make them suitable candidates for further in vivo efficacy studies. Nanodelivery of specific dsRNA for suppressing the western corn rootworm (WCR, Diabrotica virgifera virgifera) genes was studied using modified chitosan or modified polyvinylpyrrolidinone (PVP) as nanocarriers. Computational simulation studies of dsRNA with these polymers revealed that nanoparticles can be formed between dsRNA and modified chitosan and PVP polymers. Nanocarriers of hydroxylated PVP (HO-PVP) and chitosan conjugated with polyethylene glycol (PEG) were synthesized, and analyzed using IR spectroscopy. Particle sizes and morphology were evaluated using AFM and encapsulation was studied using UV spectroscopy. However, the formation of stable nanoparticles with dsRNA could not be achieved with either of the polymers, and further efforts are ongoing to discover a better nanocarrier for nanodelivery of siRNA by using chitosan-galactose nanocarrier. In our efforts to discover a novel class of tripeptidyl anti-norovirus compounds that can strongly inhibit NV3CLpro, a set of tripeptidyl molecules were synthesized by modifying the P1 - P3 of the substrate peptide including a warhead. It was found that the replacement of P1 glutamine surrogate with triazole functionality does not improve the inhibitory activities of the compounds. In addition, the synthesis of a known dipeptidyl compound (GC376) was carried out for evaluating its efficacy on feline infectious peritonitis (FIP) in cats.
Keywords: Viral protease inhibitors; Tricyclic pyrones; siRNA; Bioactive molecules; Alzheimer's disease; Tripeptidyl anti-norovirus compounds